MEDAN MAKNA PERISTILAHAN PROSESI ADAT PERKAWINAN MASYARAKAT JAWA DI RASAU JAYA - Trisnawati, Deri; Muzammil, Ahmad Rabi ul; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study with respect to the semantic field of marriage customs in particular terminology of traditional Javanese marriages procession in Rasau. Issues discussed this research is the namely terminology, component of meaning type, and semantic function. The purpose of this study describes the terminology of marriage customs. The method of this research was descriptive method. The form of this research was qualitative form. The sources data of this research was the Java language spoken by the informants form Rasau. The data of this research was the terminology of meaning field of traditional Javanese marriages procession in Rasau strating from pre-marriage, marriage, and post-marriage. The techniques of collecting data used dialogue, interview, record and notes with the data collection tool in the form of question list, list of pictures, recorder and recording card. Based on the analysis of the terminology of meaning field of traditional Javanese marriage procession in Rasau, there were 50 leksem terminology. Leksem in the pre-marriage were 15 leksem, leksem in the marriage were 30 leksem, and leksem in post-marriage were 5 leksem. The function of leksem is to explained the function of terminology starting from pre-marriage, marriage, and post-marriage.Keyword: Meaning field, Terminology, Traditional Javaneses